Analysis of alanine aminotransferase in various organs of soybean (Glycine max) and in dependence of different nitrogen fertilisers during hypoxic stress - Rocha, Marcio (Springer Vienna, 2010)
Alanine aminotransferase (AlaAT) catalyses the reversible conversion of pyruvate and glutamate into alanine and oxoglutarate. In soybean, two subclasses were identified, each represented by two highly similar members. To investigate the role of AlaAT during hypoxic stress in soybean, changes in transcript level of both subclasses were analysed together with the enzyme activity and alanine content of the tissue. Moreover, the dependency of AlaAT activity and gene expression was investigated in relation to the source of nitrogen supplied to the plants. Using semi-quantitative PCR, GmAlaAT genes were determined to be highest expressed in roots and nodules. Under normal growth conditions, enzyme activity of AlaAT was detected in all organs tested, with lowest activity in the roots. Upon waterlogging-induced hypoxia, AlaAT activity increased strongly. Concomitantly, alanine accumulated. During re-oxygenation, AlaAT activity remained high, but the transcript level and the alanine content decreased. Our results show a role for AlaAT in the catabolism of alanine during the initial period of re-oxygenation following hypoxia. GmAlaAT also responded to nitrogen availability in the solution during waterlogging. Ammonium as nitrogen source induced both gene expression and enzyme activity of AlaAT more than when nitrate was supplied in the nutrient solution. The work presented here indicates that AlaAT might not only be important during hypoxia, but also during the recovery phase after waterlogging, when oxygen is available to the tissue again.